(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
At the beginning of my article, I would like to say that learning foreign languages is especially important nowadays. Some people learn foreign languages because they need them in their work. Others travel abroad. For the thirds studying languages is a hobby. Nowadays English has become the world’s one of the most important language in politics, science, trade and cultural relations. To know English today is absolutely necessary for every educated person, for every good specialist. The reasons for learning a new language are varied, but the importance of learning foreign languages is universal: it will always benefit you in one way or another. First and foremost, one of the most important reasons to learn a foreign language is the stimulation it offers your mind.